Cognitive impairment assessment through handwriting (COGITAT) score: a novel tool that predicts cognitive state from handwriting for forensic and clinical applications - Balestrino, Maurizio; Brugnolo, Andrea; Girtler, Nicola; Pardini, Matteo; Rizzetto, Cristiano; Alì, Paolo Alessandro; Cocito, Leonardo; Schiavetti, Irene (Frontiers in Psychology, 2024)
Introduction Handwriting deteriorates proportionally to the writer’s cognitive state. Such knowledge is of special importance in the case of a contested will, where dementia of the testator is claimed, but medical records are often insufficient to decide what the testator’s cognitive state really was. By contrast, if the will is handwritten, handwriting analysis allows us to gauge the testator’s cognitive state at the precise moment when he/she was writing the will. However, quantitative methods are needed to precisely evaluate whether the writer’s cognitive state was normal or not. We aim to provide a test that quantifies handwriting deterioration to gauge a writer’s cognitive state. Methods We consecutively enrolled patients who came for the evaluation of cognitive impairment at the Outpatient Clinic for Cognitive Impairment of the Department of Neuroscience, Rehabilitation, Ophthalmology, Genetics and Maternal and Child Sciences (DINOGMI) of the University of Genoa, Italy. Additionally, we enrolled their caregivers. We asked them to write a short text by hand, and we administered the Mini Mental State Examination (MMSE). Then, we investigated which handwriting parameters correlated with cognitive state as gauged by the MMSE. Results Our study found that a single score, which we called the COGnitive Impairment Through hAndwriTing (COGITAT) score, reliably allows us to predict the writer’s cognitive state. Conclusion The COGITAT score may be a valuable tool to gage the cognitive state of the author of a manuscript. This score may be especially useful in contested handwritten wills, where clinical examination of the writer is precluded.